Colorectal Cancer Subtypes – The Current Portrait - Jordan, Peter (2019)
Colorectal cancer (CRC) is one prominent example for how chemotherapy has been changing by moving from the use of general cytotoxic agents to more tumour-specific drugs. For example, antibody-based drugs neutralize a growth factor receptor protein on the surface of tumour cells. The development of such new therapeutic opportunities requires a more thorough and systematic subclassification of CRC because tumour cells can exploit several alternative genetic pathways for their survival. This chapter gives an overview on CRC subtypes as an introduction to the following book chapters that will describe aspects of specific subtypes, and how these may lead to the development of novel pathway-specific drugs for a more precise therapeutic intervention.